Potential negative impacts and low effectiveness in the use of African annual killifish in the biocontrol of aquatic mosquito larvae in temporary water bodies - Reichard, Martin; Watters, Brian R; Wildekamp, Rudolf H; Sonnenberg, Rainer; Nagy, Béla; Polacik, Matej; Valdesalici, Stefano; Cellerino, Alessandro; Cooper, Barry J; Hengstler, Holger; Rosenstock, John; Sainthouse, Ian (Parasites & vectors, 2010)
Commentary and discussion on a recent paper promoting the use of Nothobranchius guentheri, a small African annual fish from the Island of Zanzibar as a tool to control mosquito larvae in temporary bodies of freshwater throughout Africa is presented.Arguments on major points; (1) expected low success of annual fish introductions, (2) low success of mosquito control in the field, (3) ecological threats, and (4) ethical issues are detailed.Despite serious problems with mosquito-borne diseases in tropical Africa and elsewhere, we encourage responsible means of biological control of parasite vectors. We show that effectiveness of Nothobranchius translocations is low (the previous attempts failed), likelihood of effective mosquito larvae control under field condition is negligible and ecological threats from Nothobranchius translocations from within and outside the naturally occurring range are serious. We advocate against the proposed next step of the project, i.e. field trials in Tanzania.